Social dynamics in South-West England AD 350-1150: an exploration of maritime oriented identity in the Atlantic approaches and Western channel region - Tompsett, Imogen (2012)
This research investigates the development of early medieval identities in the South West, and how various factors caused continuity and change in the insular material culture, the settlements, and ultimately in social identity. These cycles of change, brought about by influences both within and outside the region, appear to reoccur throughout the study period, and are evidenced through a regional (macro-scale) and micro-regional (site-specific) scale assessment of the evidence. An overriding sense of long-term continuity is perceived in the ability of these insular identities to retain former traditions and develop their material culture, despite the apparent political domination by far-reaching and overarching social groups in the Anglo-Saxon and Norrnan periods. These traditions include the ceramics, where an examination of developments in form and fabric have created a chronological framework that is more sympathetic to the archaeology of the region than the accepted broad periods of Early, Middle and Late Saxon, and which perhaps reflects a more accurate picture of social changes through time. Furthermore, the retention of both prehistoric and Late Roman practices, in particular the former, is seen throughout all aspects of the archaeological evidence and is examined here through the themes of settlement hierarchies, exchange mechanisms and identity, and their spatial differentiation, and with geographical determinism a deciding factor in the form and nature of communities. It is significant that prehistoric, Byzantine and Late Antique practices prevailed in the fifth to eighth centuries where Roman traditions did not, together with an introduction of Continental cultural indicators. and whilst insular traditions show similarities with those of other Atlantic regions. including Ireland. Scotland and Wales. The thesis also explores the development of Late Roman societies in an assessment of the impact of geographical determinism on identity, and the potential development of Atlantic and maritime identities within society as a whole.